Molybdenum Back-Contact Optimization for CIGS Thin Film Solar Cell - J.R. Ray; N.M. Shah; M.S. Desai; C.J. Panchal (Журнал нано- та електронної фізики)
Molybdenum (Mo) thin films are most widely used as an ohmic back-contact in the copper indium diselenide (CIS) and its alloy copper indium gallium diselenide (CIGS) based thin film solar cell. Radio frequency (RF) magnetron sputtering system used to deposit Mo thin films on soda lime glass substrate. The deposition was carried out using argon (Ar) gas at different Ar controlled (working) pressures (1 mTorr to 10 mTorr) and at different RF powers (60 W to 100 W). The influence of both the working pressure and the RF power on the Mo thin films was studied by investigating its structural, morphological, electrical, and optical measurements. The results reveal that a stress-free, low-sheet-resistance (~1 Ω/⁭cm2), and reflecting (~ 55 %) Mo thin film was observed at 1 mTorr working pressure and 100 W RF power.